Is Money the Biggest Motivator in the Workplace? What We Learn from Real-Life Facts. - Mqondisi Bhebhe (International Journal of Applied Business and International Management, 2018)
In response to Maslow’s (1943) hierarchy of needs, business executives today favour the use of non-financial rewards over money, resulting in a lot of dissatisfaction in the workplace. This paper analyses both the primary and secondary evidence, focusing on the causes of corruption, industrial strikes and the general behaviour towards money in an effort to guide employers on the best motivation technique. Findings suggest that most individuals can embark on violent and destructive behaviour if they are not paid in cash and are reluctant to fight for non-monetary rewards. However, to perfectly motivate the workforce, it concludes by recommending a mixture of both but with more emphasis on financial rewards, regardless of the individual’s corporate development level.